Growth and survival of Grindelia covasii A. Bartoli & Tortosa seedlings under water stress (Semiárida, 2018)
Grindelia covasii is an endemic species of the Lihue Calel Sierras. In this semiarid enviroment soil water availability is a limiting factor for seedling establishment. This greenhouse experiment evaluated the growth and survival of juvenile G. covasii plants by exposing four plant sizes (G=large, M=medium, and P=small plant sizes) to three irrigation levels, simulating high (Rf), moderate (R7) and low soil water availability (R14). Plant growth and physiological measurements were taken during the experiment. Results showed that growth parameters were affected by increasing water stress. Leaf senescence was high under severe water limitation (R14) with larger individuals showing highest drought tolerance. No changes were observed in resource allocation from aboveground parts to roots in response to water stress. Survival was also affected by reduced water availability, with smaller plants being the most affected. The lower tolerance of juvenile stages of G. covasii to severe water stress observed in this experiment, suggest that this species would require moist conditions for successful seedling establishment. This study provides useful information regarding G. covasii recruitment.
Keywords: seedling recruitment; endemism; water stress; Lihué Calel